Investigation of the cytotoxic potential and anti-inflammatory properties of Euphorbia hirta alone and in combination with Selenium in vitro - Pretorius, Etheresia (University of Pretoria, 2013)
Dissertation (MSc (Cell Biology))--University of Pretoria, 2009.